Transmural coil embolization—alternative technique for management of arterial perforation during subintimal angioplasty - Damodharan, Karthikeyan; Bolia, Amman (Indian Journal of Radiology and Imaging, 2016)
Subintimal angioplasty of lower limb arterial occlusion carries a relatively higher risk of vessel perforation compared to transluminal angioplasty. Vessel perforation is a potentially life threatening complication which requires prompt recognition and management. They are usually managed by endovascular techniques such as low-pressure balloon tamponade, covered stents, and coil embolization of the ruptured artery. We describe a technique of treating vessel perforation following balloon angioplasty. Patient developed a large perforation of the proximal superficial femoral artery (SFA) after balloon inflation during subintimal angioplasty of complete SFA occlusion. Following failure of balloon tamponade in sealing the perforation, we successfully treated it by deploying an embolization coil at the site of perforation through the vessel wall followed by balloon tamponade. Our technique could be a useful relatively inexpensive alternative treatment option in the management of vessel perforation compared to covered stents.
Keywords: Perforation; subintimal angioplasty; transmural coil embolisation